The Effect of Marketing Mix on Consumer Satisfaction in Tolitoli Computer Embroidery: Pengaruh Bauran Pemasaran terhadap Kepuasan Konsumen di Tolitoli Computer Embroidery - Linda Astria; Angga Prayudha Ashari H. Mallu (International Journal of Economic Entrepreneurship and Business Management, 2025)
This study aims to Influence Marketing Mix on Consumer Satisfaction in ANS Computer Embroidery Tolitoli. This study uses a type of quantitative research. The data source is in the form of primary data, namely data obtained directly through observations, interviews, questionnaires, and documentation directly related to this research. The data analysis techniques used are Data Quality Test, Classical Assumption Test, Multiple Linear Regression Analysis and SPPS Software Determination Coefficient Test version 26. Based on the results of the T-test, a T-calculation value of 5.071 products with a significant number of 0.000 was obtained, and the T-test calculated the price variable was 7.934 with a significant value of 0.000, the promotion variable was -4.407 with a significant number of 0.000 and the place variable was -3.274 with a significant number of 0.002. Therefore, it can be concluded that the variables of product, price, promotion and place partially have a significant effect on the variables of consumer satisfaction. The results of the simultaneous test obtained an F-count value of 40.579 which means that the variables free of products, prices, promotions and places together simultaneously have a significant effect on the variables tied to consumer satisfaction of ANS Bordir Tolitoli. The results of the determination coefficient test obtained a value of 0.771 or 77.1%, which means that the magnitude of the influence of the marketing mix on consumer satisfaction is 77.1%, while the remaining 22.2% is influenced by factors outside this study.